Association between the diagnosis of atrial fibrillation and aspects of health status: a Danish cross‐sectional study. Issue 3 (1st October 2015) - Hoegh, Vibeke; Lundbye‐Christensen, Soeren; Delmar, Charlotte; Frederiksen, Kirsten; Riahi, Sam; Overvad, Kim
Abstract : Background: Caring for patients living with atrial fibrillation (AF) is expected to be an increasing challenge for the healthcare sector in the future. Inconclusive results on self‐reported health‐related quality of life and health status in patients living with AF have previously been reported, ranging from being similar to those observed in patients who have sustained and survived a myocardial infarction to not being different from those of healthy subjects. In these studies, gender differences were not taken into account. Aim and objective: To investigate the association between the diagnosis of atrial fibrillation and self‐reported health status. Design: An observational, cross‐sectional study was conducted using data from the Danish Diet, Cancer and Health cohort. Information on health status was obtained using the Danish version of the Short Form 36 version 2 questionnaire. The analyses were stratified on gender. In adjusted analysis, we considered potential confounding from comorbidity expressed by the Charlson Comorbidity Index and effect modification by age. Ethical approval: The local ethical committees of Copenhagen and Frederiksberg municipalities (Approval no.: (KF) 01‐345/93) approved the study. Results: We included 42 598 participants of whom 873 had a diagnosis of AF and/or atrial flutter. We found a lower adjusted physical component score among AF patients. No systematic differences in the mental component score (MCS) were observed. Conclusion: Participants diagnosed with AF report a clinically and statistically significantly lower physical health component score. No systematic differences in the MCS were found when comparing with the remaining participants in the cohort. As healthcare professionals caring for patients living with AF are not always expecting patients living with AF to experience a burden from their disease, the individual patients' experience of their situation, feelings, preferences, symptoms and needs leading to physical limitations should always be articulated.